Range expansion of the Atlantic fish Zenopsis conchifer (Lowe, 1852), family Zeidae, in the western Mediterranean Sea - PINTO, CECILIA; ROPPO VALENTE, GIOVANNI; RASORE, NICOLA; OLMI, EDOARDO; LANTERI, LUCA; GARIBALDI, FULVIO; VIVA, CLAUDIO; NERI, ALESSANDRA; MASSARO, ANDREA; De CARLO, FRANCESCO; LIGAS, ALESSANDRO; SARTOR, PAOLO (Mediterranean Marine Science, 2023)
Three specimens of Silver John dory, Zenopsis conchifer, (Lowe, 1852) were observed for the first time in the Ligurian Sea and northern Tyrrhenian Sea (western Mediterranean), one in 2020 and two in 2021. This is the fifth record (up to ten individuals) of Z. conchifer in the Mediterranean Sea, which occurred 11 years after the last observation in 2010 in the southern Tyrrhenian Sea. The present study reports the northernmost record of the species in the western Mediterranean Sea, indicating a potential range expansion of the distribution of this Atlantic species across the area. Morphometric, meristic and biological data of the three specimens are provided and compared with previous published records.